The influence of low-temperature resistant lactic acid bacteria on the enhancement of quality and the microbial community in winter Jerusalem Artichoke (Helianthus tuberosus L.) silage on the Qinghai-Tibet Plateau - Wei, Xiaoqiang; Sun, Xuemei; Zhang, Haiwang; Zhong, Qiwen; Lu, Guangxin (Frontiers in Microbiology, 2024)
Jerusalem Artichoke (Helianthus tuberosus L.), an emerging "food and fodder" economic crop on the Qinghai-Tibet Plateau. To tackle problems such as incomplete fermentation and nutrient loss occurring during the low-temperature ensilage of Jerusalem Artichokes in the plateau's winter, this study inoculated two strains of low-temperature resistant lactic acid bacteria, Lactobacillus plantarum (GN02) and Lactobacillus brevis (XN25), along with their mixed components, into Jerusalem Artichoke silage material. We investigated how low-temperature resistant lactic acid bacteria enhance the quality of low-temperature silage fermentation for Jerusalem Artichokes and clarify its mutual feedback effect with microorganisms. Results indicated that inoculating low-temperature resistant lactic acid bacteria significantly reduces the potential of hydrogen and water-soluble carbohydrates content of silage, while increasing lactic acid and acetic acid levels, reducing propionic acid, and preserving additional dry matter. Inoculating the L. plantarum group during fermentation lowers pH and propionic acid levels, increases lactic acid content, and maintains a dry matter content similar to the original material. Bacterial community diversity exhibited more pronounced changes than fungal diversity, with inoculation having a minor effect on fungal community diversity. Within the bacteria, Lactobacillus remains consistently abundant (>85%) in the inoculated L. plantarum group. At the fungal phylum and genus levels, no significant changes were observed following fermentation, and dominant fungal genera in all groups did not differ significantly from those in the raw material. L. plantarum exhibited a positive correlation with lactic acid and negative correlations with pH and propionic acid. In summary, the inoculation of L. plantarum GN02 facilitated the fermentation process, preserved an acidic silage environment, and ensured high fermentation quality; it is a suitable inoculant for low-temperature silage in the Qinghai-Tibet Plateau.